2009
DOI: 10.1007/s11326-009-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

Unterbringungen und Beschränkungen an einer psychiatrischen Abteilung: 2003-2006

Abstract: During the years 2003 to 2006 compulsory admissions and physical restraints were recorded in a psychiatric department. During this period the rate of compulsory admissions per all psychiatric admissions rose from 29.4% in 2003 to 33% in 2006. The rate of patients with at least one episode of physical restraint rose from 2.6% to 5.6%. The rate of compulsory admissions per inhabitants of the catchment area rose from 320/100.000 inhabitants in 2003 to 411/100.000, the rate of admissions with at least one episode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In 2017, one-fifth of patients admitted to a locked unit had a diagnosis of schizophrenia and related disorders. This proportion is lower than that in other European hospitals (Rittmannsberger et al, 2009;Arnold et al, 2019). For example, the report about involuntary admissions in Austria in 2017 indicates that 23% of patients suffered from schizophrenia (Sagerschnig et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In 2017, one-fifth of patients admitted to a locked unit had a diagnosis of schizophrenia and related disorders. This proportion is lower than that in other European hospitals (Rittmannsberger et al, 2009;Arnold et al, 2019). For example, the report about involuntary admissions in Austria in 2017 indicates that 23% of patients suffered from schizophrenia (Sagerschnig et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Mean duration of stay in a locked unit was 9.3 days and again, there were no gender differences in this regard. In another Austrian hospital, schizophrenia patients’ length of stay in a locked unit was 12.6 days (Rittmannsberger et al ., 2009), and a study from Germany reported a mean duration of 13.9 days in female and 17 days in male patients without differentiating between diagnoses (Roßberg, 2010). In our previous investigation (Edlinger et al ., 2018), we found that length of stay decreased over the course of time from 1997 until 2012.…”
Section: Discussionmentioning
confidence: 99%